2004
DOI: 10.1577/t03-146.1
|View full text |Cite
|
Sign up to set email alerts
|

A Biointegrity Index (IBI) for Coldwater Streams of Western Oregon and Washington

Abstract: We developed, tested, and applied an index of biological integrity (IBI) for fish and amphibian assemblages in coldwater streams of the Oregon and Washington Coast Range. A probability sample of 104 wadeable sites was quantitatively sampled for fish and amphibian assemblages as well as physical and chemical habitat from 1994 to 1996. Natural gradients and anthropogenic disturbances were assessed by examining digital data for catchment‐scale road density and vegetation cover, along with site‐scale physical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 46 publications
3
65
0
2
Order By: Relevance
“…A similar pattern may be expected between fishery quality and the coldwater IBIs of Mundahl and Simon (1999), Mebane et al (2003), and Hughes et al (2004), which included salmonid size, abundance, recruitment metrics, or a combination thereof. Additionally, reduction in or absence of brown trout, as well as chubs and nases (both moderately sensitive), in moderately to highly disturbed cold waters is not associated with the presence of other game fishes sought by Portuguese anglers.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…A similar pattern may be expected between fishery quality and the coldwater IBIs of Mundahl and Simon (1999), Mebane et al (2003), and Hughes et al (2004), which included salmonid size, abundance, recruitment metrics, or a combination thereof. Additionally, reduction in or absence of brown trout, as well as chubs and nases (both moderately sensitive), in moderately to highly disturbed cold waters is not associated with the presence of other game fishes sought by Portuguese anglers.…”
Section: Discussionsupporting
confidence: 66%
“…Hughes et al (1998) and Mebane et al (2003) reported that their IBIs had greater among-site versus within-site variability (signal/noise) than the metrics forming them. But Hughes et al (2004) and Whittier et al (Lyons et al 1996;Mundahl and Simon 1999;Ferreira et al 2007;Whittier et al 2007). However, predictive IBI modeling (which calibrates for natural gradients in size, temperature, and elevation) does not necessarily require separation into warmwater and coldwater models (Oberdorff et al 2002;Pont et al 2006Pont et al , 2009.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, many other studies in the past used species presence/absence data for impact assessment of running waters (Fausch et al, 1984;Lyons et al, 1996;Oberdorff et al, 2002;Hughes et al, 2004;Johnston et al, 2011) either because of lacking standards in methods of sampling or lack of data due to higher costs in the sampling. In our analyses, metrics based on presence/absence (nsp) responded in all four river types (Fig.…”
Section: Metricsmentioning
confidence: 99%
“…Based on the concept of the ''index of biotic integrity'' (IBI), (Karr, 1981) and under the frame of the ''Clean Water Act'', many scientists tried to find appropriate fish metrics and fish indices for the assessment of the ecological status of running waters (Fausch et al, 1984;Lyons et al, 1996;Oberdorff et al, 2002;Hughes et al, 2004;Johnston et al, 2011). Many were successful but the results were restricted to regional extents.…”
Section: Introductionmentioning
confidence: 99%
“…A utilização de macroinvertebrados bentônicos para o desenvolvimento de índices é atualmente extremamente comum, especialmente para avaliação da integridade de rios e riachos (Barbour et al 1996, Klemm et al 2003, Böhmer et al 2004, Moya et al 2007. Além disso, outros organismos passaram a ser utilizados como bioindicadores para o desenvolvimento dos índices, como pássaros (Bryce et al 2002), anfíbios (Hughes et al 2004), macrófi tas aquáticas (Miller et al 2006), perifíton (Hill et al 2003) e fi toplâncton (Lacouture et al 2006). No Brasil, existem três trabalhos publicados em revistas internacionais que apresentam desenvolvimento de índices multimétricos: (1) para macroinvertebrados em riachos (Baptista et al 2007); (2) para peixes em rios (Araújo et al 2003, Bozzeti & Schulz 2004.…”
Section: Definição E Origem Dos íNdices Multimé-tricosunclassified